Here Comes The Sun: A Novel Portraying Quarter-life Crisis of a College Graduate - Jeremy Jordan; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
Quarter-life crisis (QLC) is a period of uncertainty and questioning that typically occurs when people feel trapped, uninspired, and disillusioned during their mid-20s to early 30s, which is the currently most discussed and concerning topic nowadays since this issue is causing problems in twenty-somethings. Using the Quarter-life Crisis theory, this thesis explores the symptoms, causes, and solutions of QLC. Using psychological realism as its genre, this novel will explore the interior life of the main character, Rei, who experiences QLC. This novel tells the story of Rei, a fresh graduate who is unemployed for six months and is pressured by his father, under the influence of societal structure, to look for a job. Through the story, it can be seen that Rei’s symptoms of QLC are anxiety, identity crisis, and depression. The causes of his QLC are high expectations from his surroundings, sudden responsibility changes, and self-doubt. Solutions to his QLC are acknowledging his own QLC, asking for help, and accepting himself.